Frequency experimental identification approach for single-phase induction motor common-mode parameters - Hakmi, Yassine; Miloudi, Houcine; Miloudi, Mohamed; Gourbi, Abdelkader; Bermaki, Mohammed Hamza (Національний технічний університет "Харківський політехнічний інститут", 2024)
The presence of broad-spectrum and high-amplitude electromagnetic interference (EMI) within a single-phase induction motor (SPIM) drive poses a significant threat to both the system and other electronic equipment. High-frequency (HF) models of electrical motors play a critical role in overcoming these challenges, as they are essential for characterizing electromagnetic compatibility (EMC) in drives and designing effective EMI filters. The novelty of this study proposes an enhanced HF motor model based on transfer functions (TFs) to accurately represent the motor’s behavior at HFs for frequency-domain analyses in the range of 100 Hz to 30 MHz. Purpose. The equivalent HF model for a SPIM is discussed in this paper. The suggested equivalent circuit describes a motor’s common-mode (CM) properties. Methodology. HF model was developed by a frequency-domain analysis utilizing an experimental setup and MATLAB software. The motor impedance analysis is based on the measurement of variations in motor characteristics as a function of frequency in the CM setup. Originality. TF has been tuned using an asymptotic identification method of Bode to match the behavior of the real impedances of the motor parameters as a function of the frequency in the CM configuration. This tuned TFs are then synthesized into a comprehensive wideband EMC equivalent circuit model using the Foster network technique, which can be then simulated in any Spice-based simulator tools. Results. The proposed mathematical model was employed to conduct simulations, and the resulting predictions were validated against experimental data. CM response of the EMC equivalent circuit at low, medium, and HFs were compared between simulations and experimental measurements using Lt-Spice simulator software. Practical value. It is observed that results show satisfactory agreement with the measurements over a large frequency bandwidth [100 Hz–30 MHz], and the equivalent model of SPIM can be cascaded with other electronic and electrical modules to form a complete single-phase electric drive system model for fast analysis and prediction of system level EMI and electromagnetic sensitivity.

Наявність широкоспектральних та високоамплітудних електромагнітних перешкод (ЕМП) в однофазному асинхронному електродвигуні (ОАЕД) становить значну загрозу як для системи, так і для іншого електронного обладнання. Високочастотні (ВЧ) моделі електродвигунів відіграють вирішальну роль у подоланні цих проблем, оскільки вони необхідні для характеристики електромагнітної сумісності (ЕМС) у приводах та проєктування ефективних фільтрів ЕМП. Новизна цього дослідження полягає в тому, що пропонується вдосконалена модель ВЧ-двигуна на основі передатних функцій (ПФ) для точного представлення поведінки двигуна на ВЧ для аналізу частотної області в діапазоні від 100 Гц до 30 МГц. Мета. У статті обговорюється еквівалентна ВЧ-модель для ОАЕД. Запропонована еквівалентна схема описує властивості двигуна у синфазному режимі (СР). Методологія. ВЧ-модель була розроблена за допомогою аналізу у частотній області з використанням експериментальної установки та програмного забезпечення MATLAB. Аналіз імпедансу двигуна заснований на вимірюванні змін характеристик двигуна в залежності від частоти встановлення СР. Оригінальність. ПФ були налаштовані за допомогою асимптотичного методу ідентифікації Боде для відповідності поведінці реальних імпедансів параметрів двигуна залежно від частоти конфігурації СР. Надалі ці налаштовані ПФ синтезуються в комплексну модель еквівалентної схеми ЕМС з використанням методу мережі Фостера, яку потім можна моделювати в будь-яких інструментах симулятора на основі Spice. Результати. Запропонована математична модель використовувалася щодо моделювання, а отримані прогнози було перевірено з урахуванням експериментальних даних. Реакція СР еквівалентної схеми ЕМС на низьких, середніх та високих частотах порівнювалась між моделюванням та експериментальними вимірами з використанням програмного забезпечення симулятора Lt-Spice. Практична цінність. Результати показують задовільне співпадіння з вимірюваннями у значному диапазоні частот [100 Гц-30 МГц], а еквівалентна модель ОАЕД може бути каскадована з іншими електронними та електричними модулями для формування повної моделі однофазної системи електроприводу для швидкого аналізу та прогнозування ЕМП на рівні системи та електромагнітної чутливості.
Keywords: common-mode; electromagnetic compatibility; experimental impedance measurement; high frequency; single-phase induction motor; синфазний режим; електромагнітна сумісність; експериментальний вимір імпедансу; висока частота; однофазний асинхронний двигун